PERFORMANSI DAN GRAMATIKA BAHASA ARAB SEBAGAI BAHASA KEDUA - Ulil Albab (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2015)
Grammar is one of the important components in studying a language. It is related to stimulate language skills includes: listening, reading, speaking, and writing. This article discusses the teaching of grammar in pesantren . The pesantren used salafiyah and modern curriculum. The study is conducted for 22 students in the last class. The method used is a correlational study. The result of the study shows that there is a positive correlation between grammatical mastery and language performance in teaching & learning Arabic. Means that grammatical mastery is one of the important factors to perform a good Arabic language.DOI: 10.15408/a.v2i1.1516